Validation, Invalidation, and Negative Speech Acts in Dementia Care Discourse - Amino, Kaoru (Frontiers in Communication, 2020)
Reflecting Japan's growing elderly population, communication between dementia patients and their family caregivers has become as much of an issue as ageism in neo-gerontology, nursing, and social work. The details of communication in dementia care are best described through the perspective of discourse analysis: theoretical concepts borrowed from applied linguistics and communication studies offer practical tools for monitoring how dementia patients experience communication with others, either domestically or professionally. Ochs (2002), e.g., adopted the theory of stance-taking to describe the interaction between an autistic child and other “normal” pupils. This discourse and the underlying power issue is analogous to the typical view of Alzheimer patients. In the field of social work, Feil (1993) defined the concept of a validation scale to gauge caregiver attitudes toward patients based on theories of individual schema, frame, and patient subjectivity. There are reciprocal versions of this concept in nursing, such as the invalidation scale suggested by Van Wheert et al. (2008). This study positions these concepts of validation and invalidation within the theoretical framework of discourse analysis, and uses them to analyze the illocutionary act or linguistic formula in communication between physicians, caregivers, and dementia patients, based on data recorded in a Japanese hospital examination room in 2016 (16 occasions; N = 58). The acts were found to correspond to: (1) psychological representation; (2) orientation and testing; (3) accusing and blaming; and (4) disruption and intruding on a patient's frame. Further analysis found an overuse of psychological verbs, which represent patients' thoughts, emotions, perceptions, and sensory status, with 50% unaccompanied by hedge as a modal marker to avoid strong subjectivity. In testing a dementia patient's cognitive status, 50% of the data contained questions that asked patients directly to report their cognitive status, requiring them to have a metacognitive awareness, or by infantilizing the patient through simple orientation. As for acts of accusation and claims about a patient's current symptoms, these included: a caregiver's extra intention as “voice” in forms of constructed speech (Tannen, 1986), deviation from the maxim of quantity (Grice, 1975), and poking fun at the patient. The results suggest that those subjectivities in caregiver and patient can be explained in relation to a social and structural power issue, which positions patients automatically as “the normal deviant” (Goffman, 1963), and positions caregivers themselves as an authority, as “the normal,” and as “representative.” From a practitioner's perspective, this framework suggests a need for introspection to acknowledge frame and subjectivity, as well as a need for compassion for the experiences of a patient's life.